Advancement in CdMnTe-based photovoltaic cells: Grain growth, deep states and device efficiency assessment with chlorine treatment. (15th January 2023) - Chander, Subhash; Tripathi, S.K.
Graphical abstract: Highlights: This communication is focused on development of CMT-based PV cells with CdCl2 treatment. Devices were fabricated having structure of ITO/CdS/CMT/Au and then chlorine treatment was performed. Devices without and with CdCl2 treatment demonstrated the efficiency of 7.83% and 8.76%. Deep trap states in the devices were analyzed with the help of Mott-Schottky plots. Grain growth was also explored with chlorine treatment by analyzing SEM images. Abstract: The suitability of the metal rear contact, the density of surface states, the rate of recombination of the absorber layer, and open circuit voltage loss are all innate issues with typical CdTe solar cells. These problems can be addressed with small Mn doping in CdTe, making it a Cd1-x Mnx Te (CMT) trinary semiconductor, which can tune the band gaps. With the purpose of give an alternative to traditional CdTe material, CMT PV cells having device structures of ITO/CdS/CMT/Au have been investigated in this study with CdCl2 treatment. The devices were fabricated by vacuum evaporation, and CMT PV cells without and with CdCl2 treatment demonstrated the efficiency of 7.83% and 8.76%. The capacitance–voltage data were also used to calculate the doping concentration and depletion layer width, while deep trap states in the devices were analyzed with the help of Mott-Schottky plots. The Quantum efficiency measurements were done at zero bias to identify the optical or electronic losses in devices with CdCl2 treatment. The grain growth was also explored with chlorine treatment by analyzing SEM images. For further improve the device performance, the states responsible for recombination must be located and eliminated to enhance the fill factor and efficiencies of the devices. The devices' repeatability was also examined and was found to be satisfactory with a 6–10% deviance. This work demonstrates the need for additional research to enhance the performance of CMT PV cells with CdCl2 treatment for usage as an affordable alternative photovoltaic source.